Individualizing training in swimming: Evidence for utilizing the critical speed and critical stroke rate concepts - Piatrikova, E.; Willsmer, N. J.; Sousa, A. C.; Gonzalez, J. T.; Williams, S. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To monitor physiological, technical, and performance responses to individualized high-intensity interval training (HIIT) prescribed using the critical speed (CS) and critical stroke rate (CSR) concepts in swimmers completing a reduced training volume program (=30 km/wk) for 15 weeks. Methods: Over the 15-week period, 12 highly trained swimmers (age 16 [1] y, height 179 [8] cm, weight 66 [8] kg) completed four 3-minute all-out tests to determine CS and the finite capacity to work above CS (D'), and four 200-m tests at CS to establish a CSR estimate. Combining CS and D', 2 HIIT sessions designed as 5×3-minute intervals depleting 60% of D' and 3×3.5-minute intervals depleting 80% of D' were prescribed once per week, respectively. An additional HIIT session was prescribed using CS and CSR as 10×150 m or 200 m at CS with 2 cycles per minute lower stroke rate than the CSR estimate. Additional monitored variables included peak speed, average speed for 150 seconds (speed150s) and 180 seconds (speed180s), competition performance and stroke length (SL), stroke count (SC), and stroke index (SI) adopted at CS. Results: At the end of the intervention, swimmers demonstrated faster CS (mean change ± 90% confidence limits: +5.4±1.6%), speed150s (+2.5 ± 0.9%), speed180s (+3.0 ± 0.9%), and higher stroke rate (+6.4 ± 3.0%) and stroke index (+4.2 ± 3.6%). D' was reduced (-25.2 ± 7.5%), whereas peak speed, SL, and SC changed only trivially. The change in the swimmers` personal best times in the first and second main event was -1.2 ± 1.3% and -1.6 ± 0.9%, respectively. Conclusion: HIIT prescribed based on the CS and CSR concepts was associated with improvements in several physiological, technical, and performance parameters in highly trained swimmers while utilizing time- and resource-efficient approach. This was achieved despite a =25% reduction in training volume.